2022
DOI: 10.4236/pp.2022.138024
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescribing Patterns and Prevalence of Surgical Site Infections in Caesarean Section Deliveries at Two Tertiary Hospitals in Lusaka, Zambia

Abstract: Introduction: A caesarean section (CS) is one of the most frequently performed obstetric surgeries in the world and its use has increased dramatically in recent years. The number of caesarean section cases worldwide has been increasing each year, and the World Health Organization (WHO) reported an excess of 10% -15% of CS procedures for all births. However, some women experience surgical site infections (SSIs) after undergoing CS delivery. This study investigated the prescribing patterns of antibiotics in CS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…β-lactam antibiotics are among the most commonly administered drugs globally, as they have an advantageous side effect profile and in many patient populations (i.e., children, the elderly, and pregnant women), they are the only suitable antimicrobials [ 62 , 63 , 64 , 65 ]. However, the development of resistance to these agents in recent years has become a serious public health concern [ 66 , 67 , 68 ]; this is especially true in low-income countries, such as Zambia, where β-lactam antibiotics are overused and misused and are often readily available without a medical prescription [ 63 , 64 , 69 ]. In addition to β-lactamases, the modification of penicillin-binding proteins (PBPs), the decreased permeability of the bacterial outer membrane, and the co-existence of several resistance mechanisms contributed to this phenomenon [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…β-lactam antibiotics are among the most commonly administered drugs globally, as they have an advantageous side effect profile and in many patient populations (i.e., children, the elderly, and pregnant women), they are the only suitable antimicrobials [ 62 , 63 , 64 , 65 ]. However, the development of resistance to these agents in recent years has become a serious public health concern [ 66 , 67 , 68 ]; this is especially true in low-income countries, such as Zambia, where β-lactam antibiotics are overused and misused and are often readily available without a medical prescription [ 63 , 64 , 69 ]. In addition to β-lactamases, the modification of penicillin-binding proteins (PBPs), the decreased permeability of the bacterial outer membrane, and the co-existence of several resistance mechanisms contributed to this phenomenon [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inappropriate use of antibiotics in humans and animals has contributed to the development and worsening of AMR . One of the major factors contributing to AMR in humans has been reported to be the ease with which antimicrobials can be obtained without a prescription. Additionally, irrational prescribing of antibiotics has made this phenomenon worse. , AMR has also been linked to irrational dispensing practices and easy access to antibiotics for use in animals without a prescription. Evidence has also shown that healthcare professionals with this responsibility have missed doses when administering antibiotics, which has been linked to the development of AMR. , As a result, patient noncompliance with antimicrobial therapy has also contributed to the development of AMR. Furthermore, a lack of patient education on antimicrobial use (AMU) and AMR is another factor that contributes to inappropriate AMU and, eventually, may lead to the development of AMR. ,, …”
Section: Introductionmentioning
confidence: 99%